CARBOHYDRATE METABOLISM DISORDERS IN THE HEART AGEING - D. U. Akasheva; I. A. Pokshubina; E. A. Plokhova; О. N. Tkacheva (Кардиоваскулярная терапия и профилактика)
The heart  itself ageing  is characterized  by structural  and  functional changes, determined just by older age, even in absence of cardiovascular pathology. Carbohydrate  metabolism disorders,  based upon the insulin resistance, are  common  in elderly, and  worsen the processes of ageing,  including the heart.  Structural  changes  in the heart are characterized  by development of concentric  remodelling of the left ventricle myocardium, and functional — by diastolic function impairment, with saved  systolic function. The review focuses  on the influence of ageing  and  carbohydrate  metabolism  disorders  on the structure   and  function  of  myocardium,  and  the  obvious  fact  is discussed, that earlier screening  and correction  of insulin resistance and glucose metabolism disorders might prevent or delay the progression of age-related heart failure.